Patient Engagement in a Hybrid Care Pathway for Hypertension: Not One Size Fits All - Job van Steenkiste MD; Iris Verberk-Jonkers MD, PhD; Stéphanie de Koning CNS; Joyce Voss-de Haan CNS; Bianca de Jong-Verhagen MSc; Daan Dohmen PhD (Journal of Patient Experience)
We evaluated current experiences and future needs for the long-term engagement of patients in a hypertension hybrid care pathway (Maasstad Hospital, NL). Patients >18 y/o with ≥3 months care pathway participation were recruited by telephone and divided into three age/focus groups with distinct digital skills and attitudes toward lifestyle interventions (group 1:18-40 y/o, group 2:40-65 y/o, group 3:>65 y/o). We used deductive thematic content analysis to cluster the results to the different digital elements (remote monitoring, communication, digital lifestyle intervention) of the care pathway. Fifteen patients were interviewed in March 2023 (Group 1;2;3, 3;6;6 participants). The care pathway improved disease insight, engagement, and shared decision capabilities in all groups. For further improved adherence and engagement, all patients indicated the need to incorporate a more personalized approach and interaction with their healthcare provider. In addition, the oldest group preferred simplification of the telemonitoring application, while the other groups preferred enrichment with more complex information. To ensure optimal engagement, digital elements in hybrid care pathways should be personalized and tailored to individual as well as to age-specific needs.